Antibiotic resistance patterns in bacteria isolated from subclinical mastitis - Chávez Rosero, Katherine (2025)
The aim of this study was to assess the resistance of bacteria isolated from subclinical mastitis in crossbred Holstein cows from the Tunshi San Nicolás Community, Chimborazo, Ecuador. Milk from the four mammary quarters of 90 lactating cows was analysed using the California Mastitis Test (CMT). Forty cows had at least one positive quarter. Bacterial culture was performed on Blood Agar and MacConkey Agar and identification was done using Gram staining and biochemical tests. The test for bacterial sensitivity and resistance to antibiotics was performed using the Kirby-Bauer protocol. Gram-positive pathogens were isolated: Staphylococcus spp (84.1%) and Streptococcus spp (15.9%), and Gram-negative pathogens: Escherichia spp (73.8%) and Klebsiella spp (26.2%). Sensitivity to gentamicin was 100% for all isolates, and to tetracycline 80.2%, while resistance was evident to penicillin with 65.4%.